Intimate partner violence and postpartum healthcare access in Kenya: a cross-sectional study - Rebecca Woofter; John Mboya; Ginger Golub; May Sudhinaraset (BMC, 2024)
Abstract Background Intimate partner violence (IPV) impacts physical health, mental health, and healthcare use. IPV during pregnancy, in particular, is associated with lower rates of antenatal care, but no studies have assessed the association between IPV and postpartum healthcare. This study aims to examine the link between IPV (emotional, physical, and sexual) and two outcomes: postpartum healthcare use and access to family planning. Methods This study uses data from a cross-sectional survey of 859 women in Nairobi and Kiambu counties in Kenya who gave birth during the COVID-19 pandemic in 2020. Results In this sample, 36% of women reported ever experiencing IPV. Of those, 33% indicated the frequency of IPV stayed the same or increased during COVID-19. Nearly 17% of women avoided postpartum healthcare and 10% experienced issues accessing family planning. Those who experienced any form of IPV during pregnancy had approximately twice the odds of avoiding postpartum healthcare compared to those who did not experience any form of IPV. Compared to those who did not experience IPV during pregnancy, experiencing sexual IPV was associated with 2.25 times higher odds of reporting issues accessing family planning. Additionally, reporting fair or poor self-rated health was associated with both avoiding postpartum healthcare and reporting issues accessing family planning. Experiencing food insecurity was also associated with avoiding postpartum healthcare. Conclusions To our knowledge, this is the first study to establish the link between IPV during pregnancy and postpartum healthcare access. During COVID-19 in Kenya, postpartum women who had experienced IPV were at increased risk of disengagement with healthcare services. Women should be screened for IPV during pregnancy and postpartum in order to better support their healthcare needs. In times of crisis, such as pandemics, policymakers and healthcare providers must address barriers to healthcare for postpartum women.